Challenges and Strategies for Online Learning and Teaching during COVID-19 in Indonesia and Afghanistan - Kayen, Hazrat Shah; Agustia, Fadla Tsania (Journal of Teaching and Learning, 2025)
The pandemic has significantly impacted many sectors of life, including higher education. The COVID-19 outbreak created significant challenges for students and lecturers, forcing them to adjust to online learning and teaching. They developed specific strategies to tackle the challenges and study normally. This study investigated the obstacles students and lecturers faced during COVID-19 online learning and teaching in a private university in Afghanistan and a public university in Indonesia. Furthermore, it explores the strategies applied during the pandemic's requirement of creating new educational environments. In addition, it compares the students' and lecturers' experiences in online learning and teaching in both countries. To obtain the data, the study employed openended questionnaires using Google Forms, which were distributed through WhatsApp and emails to students and lecturers in a public university in Indonesia and a private university in Afghanistan. Data analysis used the onlineengagement framework for higher education, filtering and generating themes into concepts. This study found that during COVID-19, both Indonesian and Afghan students and lecturers faced several hurdles and challenges. Yet, the strategies that they applied differed according to each country's social and developmental contexts. Identifying the challenges and the online teaching and learning strategy provides practical understanding for students, lecturers, and universities.